2012
DOI: 10.1039/c2cc35171d
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of atmospheric CO2 by a self-assembled decanuclear cadmium complex via unfamiliar perchlorato and carbonato bridges

Abstract: A decanuclear Cd complex has been found as a carbonate-containing capsule. The structure strongly resembles a ten-blade waterwheel with a central carbonate ligand surrounded by two superimposed Cd(5)O(5) crowns with a pentagonal antiprism-like disposition. The capsule is doubly capped by two pentadentate perchlorate anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The homogeneous metal salts Co(OAc) 2 ·4H 2 O and Al(OEt) 3 exhibited much lower reactivity (59% and 24%, entries 9 and 10) as compared to the heterogeneous Co( iii )@cage and Al( iii )@cage. Previous reports on utilizing molecular cage complexes for CO 2 cycloaddition are rare, although some molecular cages showed selective uptake of CO 2 20,30 and were able to trap CO 2 as carbonate anions within the cage framework 31. In 2014, Martinez and Dufaud demonstrated that an azaphosphatrane–hemicryptophane cage complex was able to catalyze the CO 2 cycloaddition to give styrene carbonate in 82% yield at 100 °C and 1 atm CO 2 32…”
Section: Resultsmentioning
confidence: 99%
“…The homogeneous metal salts Co(OAc) 2 ·4H 2 O and Al(OEt) 3 exhibited much lower reactivity (59% and 24%, entries 9 and 10) as compared to the heterogeneous Co( iii )@cage and Al( iii )@cage. Previous reports on utilizing molecular cage complexes for CO 2 cycloaddition are rare, although some molecular cages showed selective uptake of CO 2 20,30 and were able to trap CO 2 as carbonate anions within the cage framework 31. In 2014, Martinez and Dufaud demonstrated that an azaphosphatrane–hemicryptophane cage complex was able to catalyze the CO 2 cycloaddition to give styrene carbonate in 82% yield at 100 °C and 1 atm CO 2 32…”
Section: Resultsmentioning
confidence: 99%
“…spheric carbon dioxide under strong basic conditions by incorporation into transition metal complexes is now very well documented. [35][36][37] Fixation of more than one carbonate unit by one molecule is much rarer. In such cases, these species usually act essentially as spacers between metals or are subtended by metal ions conforming the external surface of a cage.…”
Section: Description Of Structuresmentioning
confidence: 99%
“…21 Solid state structures of the related free ligand structures derived from 2-aminophenol and imidazole-, pyrrole-and pyridine-2-carboxaldehyde have been also reported. [22][23][24][25] With only metal complexes of ligands (e) and (h) previously reported, 18,20 literature related to the solid state structures of tridentate O,N,N 0 -1-methyl-2-imidazolephenol Schiff base molecules is scarce. There are no free ligand structures reported for this class of compound.…”
Section: Introductionmentioning
confidence: 99%